(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Urbanization as an outcome of economic liberalization together with globalization hasprompted the production and promotion of large integrated townships in India. This paper examinesvarious forces for the development of “private sector-led urban development projects” in India. Weassert that these include diverse reasons varying from the global, provincial and local scale thatcan aid to describe the expansion of these mega projects in India. These fast-growing real estatemega-projects have created a huge demand for property in peripheral locations of big citiesprompting commoditization and monetization of land. The expansion of large- scale for-profit realestate megaprojects has led to the privatization of urban space. The pragmatic analysis is derivedfrom interviews with town planning officials, urban planning professionals, user groups anddevelopers with relevant published literature in journal articles and books. The expansion of largescale urban integrated mega-projects in India necessitates a multi-scale examination of theinteractions between market, state and society. This paper propagates for a more holistic planningapproach required for spreading the benefits of large scale private sector-led urban developmentprojects among diverse socio-economic groups.